Maqamat Nawawi Al-Bantani: A Conceptual Synthesis with Self Psychology in Handling NPD (Jurnal Pemikiran Islam, 2025)
Contemporary discussions on narcissistic personality disorder (NPD) are predominantly framed within clinical psychology, with limited engagement with ethical and spiritual perspectives derived from classical Islamic thought. Existing interdisciplinary studies on Islamic psychotherapy often remain normative and lack systematic conceptual integration with established psychological theories. This study addresses this gap by offering a conceptual synthesis between Heinz Kohut’s self-psychology and the maqamat framework of Syekh Nawawi al-Bantani. Using qualitative hermeneutic analysis and a comparative mapping approach, the study examines functional correspondences between Kohut’s psychodynamic principles and selected maqamat, focusing on their roles in ego regulation, self-cohesion, and empathy formation in relation to narcissistic pathology. Rather than proposing a therapeutic model, the analysis demonstrates how maqamat Nawawi al-Bantani can be interpreted as structured psychospiritual mechanisms that parallel key psychological functions identified in self-psychology. The originality of this study lies in its method of functional comparison, which enables interdisciplinary dialogue while preserving epistemological boundaries between psychology and Sufism. By reframing Sufi ethical concepts within a systematic analytical framework, the study contributes theoretically to the literature on NPD, self-psychology, and Islamic psychology, without making claims of empirical or clinical effectiveness.